FACTORS AFFECTING THE PURCHASE DECISION OF AEROSTREET SHOES AMONG MUSLIM CONSUMERS IN PACITAN REGENCY - Malta Anantyasari (Published by the Faculty of Economics and Business, University of Labuhanbatu, North Sumat, 2025)
PURPOSE - This study aims to analyze the influence of brand awareness, price perception, and product quality on the purchasing decisions of Aerostreet shoes among Muslim consumers in Pacitan Regency. The background of this research is based on the increasing competition in the local footwear industry, where Aerostreet, as a local brand, needs to understand the factors that influence consumer buying behavior. METHODOLOGY - This research uses a quantitative approach with a survey method by distributing questionnaires to 100 respondents who have purchased Aerostreet shoes. The data analysis technique used is multiple linear regression.FINDING - The results indicate that variable brand awareness, price perception, and product quality has a positive and significant effect on the purchasing decision of Aerostreet shoes. This research is expected to provide strategic input for local business actors to enhance the competitiveness of their products in the domestic market. In conclusion, understanding consumer perceptions and preferences is crucial for building brand loyalty and sustaining business growth in a competitive market